2016
DOI: 10.1111/clr.12839
|View full text |Cite
|
Sign up to set email alerts
|

The influence of locally applied granulocyte‐colony stimulating factor on osteoporotic bone

Abstract: The results indicated that in osteoporotic bone, G-CSF may advance bone healing in cranial bone where spontaneous bone formation was insufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Improved bone formation was also seen in several studies which have locally applied G-CSF to the defect site (Ishida et al, 2010 ; Minagawa et al, 2014 ; Liu et al, 2017a , b ). In particular, Ishida et al demonstrated an increased capillary density in the bone defect, detected after local G-CSF administration but also in a control group receiving sc G-CSF.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Improved bone formation was also seen in several studies which have locally applied G-CSF to the defect site (Ishida et al, 2010 ; Minagawa et al, 2014 ; Liu et al, 2017a , b ). In particular, Ishida et al demonstrated an increased capillary density in the bone defect, detected after local G-CSF administration but also in a control group receiving sc G-CSF.…”
Section: Discussionmentioning
confidence: 71%
“…In the context of bone regeneration, Ishida et al ( 2010 ) demonstrated that treatment of a segmental bone defect in the rabbit ulna with a G-CSF loaded gelatin hydrogel resulted in accelerated bone formation. In line with this, it was shown that local delivery of G-CSF to osteoporotic bone fractures (Liu et al, 2017b ) and a rat calvarial defect (Minagawa et al, 2014 ) promoted new bone formation in both models. Assuming that an enhanced accumulation of stem cells in the circulation would facilitate their homing capacity, Marmotti et al ( 2013 ) investigated the effect of preoperative administration of G-CSF in patients undergoing high tibial valgus osteotomy with bone graft substitution.…”
Section: Introductionmentioning
confidence: 74%